Implementasi Metode ABCD dalam Kegiatan Nuzulul Qur’an sebagai Sarana Pendidikan Nonformal dan Pemberdayaan Pemuda di Desa Wedoroklurak Kabupaten Sidoarjo - Nazwa Nurul Izzah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This activity was motivated by the condition of the community in Wedoroklurak Village, which has a very strong religious life, but the implementation of religious activities in the area is still considered less than optimal. This community service activity used a descriptive qualitative approach using the Assessment-Based Community Development (ABCD) method. The service location was Wedoroklurak Village, Candi District, Sidoarjo Regency, East Java Province. The results of the community service activity indicate that the community of Wedoroklurak Village is highly religios, but still faces limitations in organizing religious activities at the village level. This is due to unequal participation, where religious activities have so far been carried out only by mothers, while adolescents have not actively participated in these activities. The Nuzulul Qur'an activity in Wedoroklurak Village aims to foster a love and deeper understanding of Islamic teachings from an early age. This activity also aims to explore and develop the potential of the children of Wedoroklurak Village through a fun and competitive approach, thereby forming a superior and competitive generation based on Islamic values.